Role of Paralogue of XRCC4 and XLF in DNA Damage Repair and Cancer Development - Tang, Jialin; Li, Zhongxia; Wu, Qiong; Irfan, Muhammad; Li, Weili; Liu, Xiangyu (Frontiers in Immunology, 2022)
Non-homologous end joining (cNHEJ) is a major pathway to repair double-strand breaks (DSBs) in DNA. Several core cNHEJ are involved in the progress of the repair such as Ku70 and 80, DNA-PKcs, Artemis, XRCC4, DNA Ligase IV and XLF. Recent studies have added a number of new proteins during cNHEJ. One of the newly identified proteins is Paralog of XRCC4 and XLF (PAXX), which acts as a scaffold that is required to stabilize the Ku70/80 heterodimer at DSBs sites and promotes the assembly and/or stability of the cNHEJ machinery. PAXX plays an essential role in lymphocyte development in Xlf deficient background while Xlf/Paxx double deficient mouse embryo died before birth. Emerging evidences also show a connection between the expression levels of PAXX and cancer development in human patients, indicating a prognosis role of the protein. This review will summarize and discuss the function of PAXX in DSBs repair and its potential role in cancer development.